The Creative Economy and Its Implications for the Brazilian Art Market: The Case of SP-Arte - Seabra, Jessica; Busnardo Filho , Antonio; Justo, Vicente Paulo (National Journal of City Management, 2024)
This article examines recent transformations in cultural discourse, particularly concerning issues of the creative economy and its impact on the contemporary Brazilian art market, using SP-Arte as a case study. The analysis highlights the integration of cultural industries into new processes of subordination and assimilation, characterized by the aestheticization of the social sphere. Grounded in a literature review and data analysis, the research explores the concept of the "creative industry" and investigates recent production modes at SP-Arte, emphasizing its "biennialization" features—such as curated sectors and educational functions—and its internationalization strategies. The study examines the interrelation between culture and economy, contributing to a deeper understanding of the transformations within the contemporary art market and cultural policies in Brazil. Additionally, the article underscores challenges related to the exclusion of smaller agents and the gentrification of urban spaces that host services and businesses tied to the art system in São Paulo. The research provides theoretical tools for analyzing similar cultural events, broadening the debate on the interaction between cultural practices, market dynamics, and public policies.
Keywords: Contemporary art; Creative industry; Creative economy